A nonlinear multi-stable piezomagnetoelastic harvester array for low-intensity, low-frequency, and broadband vibrations. (1st May 2019) - Lai, Siu-Kai; Wang, Chen; Zhang, Lin-Hao
Highlights: A compact multi-stable piezomagnetoelastic energy harvester array is proposed. The multi-stable nonlinearity can be exploited under low-intensity excitations. All generators can work simultaneously with a wide effective bandwidth. The bandwidth is expanded under the low acceleration with low frequencies. Abstract: A compact nonlinear multi-stable piezomagnetoelastic energy harvester array (MPEHA) is presented in this paper to scavenge energy from low-amplitude (<3 m/s 2 ) and low-frequency (<20 Hz) ambient vibrations. The proposed MPEHA consists of two new types of nonlinear piezomagnetoelastic harvesters, one with a tri-stable configuration and the other one with a mono-stable configuration. They are arranged alternately in the MPEHA. The tip magnet on each harvester generates a nonlinear repulsive force in-between. This repulsive force leads to two interaction modes between adjacent harvesters and makes all harvesters in the MPEHA work simultaneously, as long as one of them can produce sustained responses with a relatively large amplitude. This interaction mechanism can exploit the advantages of tri-stable harvesters, which otherwise are not working under low-intensity excitations, to improve the harvesting efficiency and extend the operating bandwidth to lower frequencies. In addition, by combining the effective operating bandwidth of each nonlinear harvester, the MPEHA can produce sustained large-amplitude electric responses over a wide frequency bandwidth without depending on its initial conditions. The lumped parameter model of the MPEHA is established and the repulsive force between adjacent harvesters is derived in a closed form. Experiments are performed to verify the proposed idea, the theoretical predictions, and to demonstrate the advantages of the MPEHA over the nonlinear multi-stable energy harvesters. The results show that, in comparison to conventional nonlinear energy harvesters, the MPEHA can produce a wider, more continuous and sustained operating bandwidth as well as low frequencies under low-intensity excitations.